Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s00402-013-1685-x
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of dynamic stabilization on the adjacent disc to a rigid instrumented level. An in vitro biomechanical analysis

Abstract: The raise of intradiscal pressure at the adjacent segment to a rigid instrumented segment can be reduced when the rigid construct is augmented with a dynamic stabilization device. Hybrid constructs might have a possible protecting role preventing the occurrence of degenerative disc changes at the adjacent segment to a rigid instrumented level. Augmentation with a dynamic stabilization device might protect the disc above a rigid rod pedicle screw construct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Based on posterior dynamic stabilization system reported by Khoueir et al [12], the Dynesys construct belongs to hybrid stabilization device; Wallis and DIAM belong to posterior interspinous device. Similar biomechanical characteristics include decreased IDP and limited [31, 38, 39, 41, 42] but still preserve some ROM at HSP/IPD instrumented level.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Based on posterior dynamic stabilization system reported by Khoueir et al [12], the Dynesys construct belongs to hybrid stabilization device; Wallis and DIAM belong to posterior interspinous device. Similar biomechanical characteristics include decreased IDP and limited [31, 38, 39, 41, 42] but still preserve some ROM at HSP/IPD instrumented level.…”
Section: Discussionmentioning
confidence: 77%
“…Schmoelz et al [38] reported Dynesys does not change IDP at proximal adjacent disc after fixation under moment-controlled mode, while Cabello et al [39] reported Dynesys decreases 50% of the IDP at instrumented level and increases 10% of the IDP at supra-adjacent level under load-controlled mode. Different controlled modes in biomechanical testing may explain these diverse results [40].…”
Section: Discussionmentioning
confidence: 99%
“…11 In addition, other study assessed the intradiscal pressure (IDP) in monosegmental fusion at L5-S1 and hybrid surgery (Dynesys at L4-5 and rigid fixation at L5-S1). 12 The IDP at the segment adjacent to the fusion was reduced when a dynamic stabilization system was added above the segment that underwent fusion. They concluded that hybrid surgery might have a possible pre- 13 The results were that the incidences of disc degeneration and spinal canal stenosis were significantly lower in PLIF with the Graf band group.…”
Section: Discussionmentioning
confidence: 99%
“…[26] Another study showed that at the level adjacent to the superior attachment, intradiscal pressure was reduced when a less rigid construct was implemented. [43] Despite the length of the construct, more flexible systems are able to avoid pressure changes at the adjacent level. The construct used in the current study allowed for more similar loading above the construct and between construct attachment points, resulting in no significant intradiscal pressure changes at the level adjacent to the superior attachment site or within the construct region.…”
Section: Discussionmentioning
confidence: 99%